The thermal conductivity measurements of solid samples by heat flux differantial scanning calorimetry - Koek, M.; Aydogdu, Y. (Amer Inst Physics, 2007)
The thermal conductivity of polyvinylchloride (PVC), polysytrene (PS) and polypropylene (PP) were measured by heat flux DSC. Our results are in good agreement with the results observed by different methods.
6th International Conference of the Balkan-Physical-Union -- AUG 22-26, 2006 -- Istanbul, TURKEY
Keywords: DSC; thermal conductivity polyvinylchloride; polysytrene and polypropylene